Effects of Barefoot and Shod on the In Vivo Kinematics of Medial Longitudinal Arch During Running Based on a High-Speed Dual Fluoroscopic Imaging System - Su, Wanyan; Zhang, Shen; Ye, Dongqiang; Sun, Xiaole; Zhang, Xini; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2022)
Shoes affect the biomechanical properties of the medial longitudinal arch (MLA) and further influence the foot’s overall function. Most previous studies on the MLA were based on traditional skin-marker motion capture, and the observation of real foot motion inside the shoes is difficult. Thus, the effect of shoe parameters on the natural MLA movement during running remains in question. Therefore, this study aimed to investigate the differences in the MLA’s kinematics between shod and barefoot running by using a high-speed dual fluoroscopic imaging system (DFIS). Fifteen healthy habitual rearfoot runners were recruited. All subjects ran at a speed of 3 m/s ± 5% along with an elevated runway in barefoot and shod conditions. High-speed DFIS was used to acquire the radiographic images of MLA movements in the whole stance phase, and the kinematics of the MLA were calculated. Paired sample t-tests were used to compare the kinematic characteristics of the MLA during the stance phase between shod and barefoot conditions. Compared with barefoot, shoe wearing showed significant changes (p < 0.05) as follows: 1) the first metatarsal moved with less lateral direction at 80%, less anterior translation at 20%, and less superiority at 10%–70% of the stance phase; 2) the first metatarsal moved with less inversion amounting to 20%–60%, less dorsiflexion at 0%–10% of the stance phase; 3) the inversion/eversion range of motion (ROM) of the first metatarsal relative to calcaneus was reduced; 4) the MLA angles at 0%–70% of the stance phase were reduced; 5) the maximum MLA angle and MLA angle ROM were reduced in the shod condition. Based on high-speed DFIS, the above results indicated that shoe-wearing limited the movement of MLA, especially reducing the MLA angles, suggesting that shoes restricted the compression and recoil of the MLA, which further affected the spring-like function of the MLA.